Automated rendezvous and docking of spacecraft - Fehse, Wigbert (Cambridge University Press, 2003)
The definitive reference for space engineers on all issues related to rendezvous and docking/berthing (RVD/B), this book provides an overview of the major issues governing approach and mating strategies, and system concepts for rendezvous and docking/berthing. Written for aerospace engineers, students and newcomers to the field.
Keywords: Orbital rendezvous (Space flight); Space vehicles -- Automatic control.; Space vehicles -- Docking.; elektronické knihy; electronic books